Considerations on privacy and intimacy: biometric security technologies - F. E. Pirolo, Heitor (FCL-UNESP Laboratório Editorial, 2012)
This article aims at reflecting on the meaning of the relationshipbetween life and politics, more specifically on biopolitics in Western societies, tounderstand how this relationship is presented when considering the existence and the legal and political forms of maintenance of Biometric Security Systems. We focus on the understanding of the increased use of security technologies through the analysis of biometric data of individuals and populations.